Analisis Karekteristik Produk Halal Pada Makanan Dalam Perspektif Ayat Ahkam - Maskur Maskur Maskur (STAI La Tansa Mashiro, 2023)
Food is not only important to meet human needs for food, but food is also closely related to culture, including technology, social organization as well as societal trust. Consumption of food is a logical consequence of human existence as living beings. Shari'at views that the consumption of food within its minimum limit to maintain existence and preserve life is an obligation, especially if the motivation and purpose of consuming food is to generate energy to carry out the rituals of Shari'ah worship. The formulation of the main problems of this study are: what is the product halal in food in the perspective of the verses of ahkam? what are the characteristics of halal products in food in the perspective of the verses of ahkam? The study in this paper uses normative legal research methods with a conceptual approach, because what is studied in this paper is the concept of halal certification and labeling which is reviewed from a juridical and normative view of Islamic law in the perspective of verse ahkam. The juridical analysis departs from ahkam verses related to the halal aspect of food. The results of this study indicate that halal products in food are halal products that have been declared halal in accordance with Islamic law and according to the verses of the Koran which explains the syar'i law or determines (istinbat) syar'i law based on these verses. Halal products have characteristics that become a reference, namely the nature, origin, as well as ways of processing food that indicate Muslim consumers. The criteria for halal eating in Islamic law such as; does not contain pork and ingredients derived from pork, not intoxicating or not khamr or its derivative products, Materials derived from animals must come from halal animals and slaughtered according to Islamic law, not included in the unclean category such as carrion, blood, dirt and others; and all storage, sale, processing, management and means of transportation for halal products may not be used for pigs or non-halal goods. If it has been used for pork or other non-halal and then it will be used for halal products, then it must first be cleaned according to the method regulated according to Islamic law.Keyword: characteristics, halal products, food, ahkam verses